Effect of postmortem ageing time on corriedale and crossbreed sensory lamb meat quality - Bianchi, G.; Bentancur, O.; Garibotto, G.; Feed, O.; Franco, J.; Señudo, C. (Agrociencia Uruguay, 2006)
The effect of lamb genetic type (pure Corriedale and Hampshire Down x Corriedale) and ageing time (1, 2, 4, 8, and 16 days) on sensory meat quality by consumers (Semitendinosus, Semimembranosus and Gluteo biceps muscle) was studied on 50 lambs carcasses (17.7 ± kg hot weight). The consumers detected differences in tenderness due to genotype and muscle type. Corriedale lambs had more tender meat that their crossbred counterparts only at 1 day of aging (5.90 vs 5.38, respectively; p≤0.05). Semitendinosus was detected more tender (scale: 1-10), tasted better and had higher overall acceptance than Semimembranosus (p≤0.01) with the Gluteus showing intermediate values according to consumers panels. Interaction between muscle type and aging was highly significant (p≤0.0001) for all meat attributes evaluated by the consumer panel. Differences in those attributes tended to decrease (tenderness) or disappear (taste and overall acceptance) with aging time. Therefore, as suggested by these results, postmortem aging of meat at 4º C was important to overcome differences in quality of lamb meat, contributing to homogenize products of different muscle types.